The reality and prospects of supply chains in light of digital transformation and its impact on the sustainable Business environment in Palestine - Hakawat, Moatasem; Khefacha, Islem (Edelweiss Applied Science and Technology, 2025)
This study investigates the current state and future prospects of supply chains under digital transformation and examines their impact on sustainable business practices in Palestine. The purpose of the study is to provide insights into how digital tools contribute to improving supply chain resilience and sustainability. Adopting a descriptive–analytical design, data were collected through a survey of 100 managers from 49 companies listed on the Palestine Stock Exchange, representing executive, purchasing, marketing, and IT functions. The data were analyzed using Smart-PLS4 and SPSS v26 to evaluate the relationship between digital adoption and sustainability outcomes. The findings reveal that digital transformation significantly enhances supply chain performance, with a strong positive correlation (p ≤ 0.05) between digital integration and economic sustainability. The results further emphasize the role of emerging technologies in fostering resilience, efficiency, and transparency. The study concludes that accelerating digital adoption is essential for building sustainable business environments in Palestine. Practically, the research suggests that greater investment in artificial intelligence, machine learning, and financial technology (FinTech) can strengthen supply chain operations and support long-term sustainability objectives.